Variable Subarray Beamforming in Low Earth Orbit Satellite Feeder Link MIMO - Koyo Tategami; Daisuke Goto; Kiyohiko Itokawa; Fumihiro Yamashita (IEEE Access)
In the future low earth orbit (LEO) satellite constellation system in the 6G era, it is essential to increase the feeder link capacity. MIMO (Multiple-Input Multiple-Output) transmission is attracting attention as a method to increase the capacity. In the case of MIMO transmission in LEO satellite feeder links, the channel transmission capacity degradation due to satellite movement and the degradation of transmission quality due to an increase in the peak-to-average power ratio (PAPR) during beamforming at the satellite side are issues that need to be resolved. This paper proposes variable subarray beamforming (VS-BF) for MIMO transmission in LEO satellite feeder links, which reduces transmission quality degradation due to PAPR and improves capacity. This paper shows that the proposed method improves channel capacity by a factor of 2 compared to the conventional method with fixed subarrays and reduces the required output backoff by 2 dB achieving BER $= 10^{-4}$ compared to full array beamforming by computer simulations.